2019
DOI: 10.1103/physrevb.100.195417
|View full text |Cite
|
Sign up to set email alerts
|

Removing all periodic boundary conditions: Efficient nonequilibrium Green's function calculations

Abstract: We describe a method and its implementation for calculating electronic structure and electron transport without approximating the structure using periodic super-cells. This effectively removes spurious periodic images and interference effects. Our method is based on already established methods readily available in the non-equilibrium Green function formalism and allows for nonequilibrium transport. We present examples of a N defect in graphene, finite voltage bias transport in a point-contact to graphene, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…It is based on the non-equilibrium Green function formalism which allows biased calculations. TRAN-SIESTA has been completely re-written and now uses advanced inversion algorithms, enables N e ≥ 1 electrodes, allows thermo-electric calculations, performing real-space calculations (without k-points) and adds phonon transport calculations using the Hessian 98,99 ,…”
Section: J Transiestamentioning
confidence: 99%
See 2 more Smart Citations
“…It is based on the non-equilibrium Green function formalism which allows biased calculations. TRAN-SIESTA has been completely re-written and now uses advanced inversion algorithms, enables N e ≥ 1 electrodes, allows thermo-electric calculations, performing real-space calculations (without k-points) and adds phonon transport calculations using the Hessian 98,99 ,…”
Section: J Transiestamentioning
confidence: 99%
“…A recent addition to the TRANSIESTA package is the use of real space self-energy terms 99,103 . These self-energies are semi-infinite in more than 1 direction and can thus be used as surrounding electrodes, for e.g.…”
Section: J Transiestamentioning
confidence: 99%
See 1 more Smart Citation
“…The method can be immediately applied to take into account, for example, complex local gating or multi-probe transport, in order to make further analysis for transport experiments or even reliable predictions. We note some recent studies working on developing numerical techniques that allow large-scale efficient transport simulations [47][48][49], but scaling the graphene lattices with an appropriately chosen scaling factor depending on the superlattice periodicity seems to be of least technical complexity and is readily applicable to anyone who is familiar with quantum transport using, for example, real-space Green's function method [32] or the popular open-source python package KWANT [50].…”
Section: Discussionmentioning
confidence: 99%
“…The density-functional and transport calculations (see Supplemental Material [11]) were carried out for a simplified quasi-one-dimensional Au tip on top of a free finite graphene sheet [Fig. 3(a)] [13,14]. They showed that the relaxation of the junction geometry prefers the top-C position to the hollow (by ≈0.2 eV) and bridge (by ≈0.04 eV) site of the graphene honeycomb cell.…”
mentioning
confidence: 99%